A Comparative Analysis Between Rectangular And Circular Structures Using Various Number Of Resonator Coil System For Wireless Power Transfer - Irshad, Talha (2019)
WPT system is an alternative and promising candidate for the charging need of many electrical devices and equipment such as electric vehicles, biomedical implants, portable tools, smartphones and network sensors. The most widely used WPT techniques are inductive coupling and MRC (MRC). In this thesis, modeling and analysis of mid-range and mid-power four-resonator coil system for WPT is presented. In the proposed system, comparative analysis of efficiency and transferred power for different coil structures i.e. rectangular and circular using different coil topologies such as two-coil, three-coil and four-resonator coil have been carried out. The proposed system is simulated using the Keysight ADS tool and later verified by fabricating a prototype. From the results, the power transmission efficiency (PTE) and the transferred power in the proposed four-resonator coil system are 74.670% and 3.8 W for circular coil structure, and 81.487% and 4.7 W for rectangular coil structure at 13-cm transmission distance between the coils respectively. Therefore, from the above measurements of PTE and Transferred Power, it is evident that in terms of coil structure, the rectangular structure has better performance than the circular one. While four-coil WPT system architecture gives the highest efficiency and transferred power at 120 kHz resonance frequency. The measured results are well agreed with simulation results with a little deviation. The findings of this research show that the four-resonator coil system with a rectangular structure is the most desirable option for efficiency requirements above 70%.